Clinically relevant biomechanics of the knee capsule and ligaments - Halewood,C; Amis,AA (Knee Surgery, Sports Traumatology, Arthroscopy, 2015)
The paper describes the concepts of primary and secondary restraints to knee joint stability and explains systematically how the tibia is stabilised against translational forces and rotational torques in different directions and axes, and how those vary across the arc of flexion–extension. It also shows how the menisci act to stabilise the knee, in addition to load carrying across the joint. It compares the properties of the natural stabilising structures with the strength and stiffness of autogenous tissue grafts and relates those strengths to the strength of graft fixation devices. A good understanding of the biomechanical behaviour of these various structures in the knee will help the surgeon in the assessment and treatment of single and multi-ligament injuries.